1174. Liposomal Co-Formulation of MPL and QS-21 Favors the Development of T-helper 1 Cells and Promotes the Induction of CD8+ T Cells Against SARS-CoV-2. (15th December 2022) - van Haren, Simon D; Thomas, Sanya; Levy, Ofer; Sanchez-Schmitz, Guzman; Doss-Gollin, Simon; Rodriguez, Yamile Lugo
Abstract: Background: Benefit of COVID-19 vaccines is limited by need for freezing, high cost, requirement for multiple boosters, and waning immunity. An unmet need for safe and effective vaccines that can be quickly deployed worldwide during a pandemic exists. A barrier to developing scalable low-cost vaccines is the restricted access to vaccine- or adjuvant-formulations due to protection by intellectual property rights. This limits research to understand their mechanism of action and potential applicability towards vulnerable populations or emerging pathogens. Methods: We studied cellular and molecular mechanisms of action of adjuvant formulations developed for global open access in 4 distinct but complementary in vitro platforms that are human, age-specific, and enable the same individual to serve as control and test condition; generating data on adjuvant-induced responses in vitro that predict activity in vivo . Results: Whole blood assay that models magnitude of innate immune activation and identifies cell types activated showed that liposomal co-formulation of MPL+QS-21 activated monocytes and natural killer cells and induced cytokine production; tissue construct assay that models monocyte extravasation and autonomous differentiation into dendritic cells (DC) showed that only MPL+QS-21 co-formulation promoted CD14+ cells towards DC phenotype; monocyte-derived DC (MoDC) assay that interrogates immune activation type showed that MPL+QS-21 co-formulation in lipid nanoparticles promoted MoDC maturation by increasing CD40, CD86, CCR7 and HLA-DR expression and Th1-polarizing cytokine secretion; and dendritic cell-T cell interface assay that assesses potential of formulations to re-activate SARS-CoV-2 Spike antigen-specific T cells showed that only MPL+QS-21 co-formulation enhanced activation of antigen-specific CD4+ and CD8+ T cells. Conclusion: Thus, human in vitro modeling provides new insight into the mechanism of action and synergistic effects of MPL+QS-21, and positions us to study them in vulnerable populations to assess potential age-specific application on vaccine development. Precision vaccinology coupled with global access may enable marked public health progress by accelerating, de-risking, and advancing affordable adjuvanted vaccines to the most vulnerable. Disclosures: All Authors : No reported disclosures.